Functional Connectivity of the Dorsal Striatum in Female Musicians - Tanaka, Shoji; Kirino, Eiji (Frontiers in Human Neuroscience, 2016)
The dorsal striatum (caudate/putamen) is a node of the cortico-striato-pallido-thalamo-cortical (CSPTC) motor circuit, which plays a central role in skilled motor learning, a critical feature of musical performance. The dorsal striatum receives input from a large part of the cerebral cortex, forming a hub in the cortical-subcortical network. This study sought to examine how the functional network of the dorsal striatum differs between musicians and nonmusicians. Resting state functional magnetic resonance imaging (fMRI) data were acquired from female university students majoring in music and nonmusic disciplines. The data were subjected to graph theoretical analysis and functional connectivity analysis. The graph theoretical analysis of the entire brain revealed that the degree, which represents the number of connections, of the bilateral putamen was significantly lower in musicians than in nonmusicians. The functional connectivity analysis indicated that compared with nonmusicians, musicians had significantly decreased connectivity between the left putamen and bilateral frontal operculum and between the left caudate nucleus and cerebellum. In conclusion, compared with nonmusicians, female musicians have a smaller functional network of the dorsal striatum, with decreased connectivity. These data are consistent with previous anatomical studies reporting a reduced volume of the dorsal striatum in musicians and ballet dancers. To the best of our knowledge, this is the first study suggesting that long-term musical training results in a less extensive or selective functional network of the dorsal striatum.